Anatomia do lenho de seis espécies de Ormosia (Leguminosae) da Amazônia - Loureiro, Arthur Araújo; Lisbôa, Pedro Luiz Braga (Acta Amazonica, 1979)
This paper presents the macroscopical and microscopical descriptions of the structure of wood of the following amazonian species of Leguminosae: Ormosia coccinea, Ormosia costulata, Ormosia flava, Ormosia macrocalyx, Ormosia nobilis and Ormosia paraensis. 18 illustrations of the woods described, 6 esquematic prints of different shapes of vascular elements encountered in the species studied, common uses and a list of principals anatomical characteristics are included in this paper.